Variability of test match cricket and the effects of match location on physical demands in male seam bowlers. (4th March 2022) - Bliss, Alex; Ahmun, Rob; Jowitt, Hannah; Scott, Phil; Callaghan, Samuel; Jones, Thomas W.; Tallent, Jamie
ABSTRACT: The physical demands of test match cricket in seam bowlers during fielding are currently unknown. Similarly, analysis of between-match variability and the effects of playing home vs. away is required. Nine international male seam bowlers across 28 test matches (n = 9 home; n = 19 away) were investigated over five years (2015–2019). Seam bowlers wore global positioning sensors during match play fielding to quantify physical demands. Absolute and relative (per hour) distances covered in five velocity bands, total distance, and number of accelerations and decelerations were assessed for each match. Coefficient of variation (CV%) and smallest worthwhile change were used to calculate between-match variability. Mixed linear modelling was used to analyse home vs away matches. Seam bowlers covered up to 50 km, with maximal durations of >21 hours during test match fielding. Small between-match CV% (8.3) were found for maximal velocity with large (CV% = 21–192) between-match variability across most other variables. Greater distances were covered at 15–20 km·h −1 (p = 0.02) and >25 km·h −1 (p = 0.04) when playing at home. The results demonstrated substantial, highly variable physical demands. Practitioners should adapt training retrospectively to the match demands encountered and should anticipate that match intensity may be higher during home matches.